Livelihood Diversity of Rural Communities Without Legal Access to Forest Resources: The Case of Kerinci Seblat National Park in Bengkulu Province - Widiono, Septri; Wahyuni, Ekawati Sri; Kolopaking, Lala M.; Satria, Arif (Forestry Faculty, Universitas Hasanuddin, 2024)
Kerinci Seblat National Park in Bengkulu, Indonesia, was gazetted by the Indonesian government, and its overlaps with forests occupied by most indigenous communities made their farming activities in the area illegal. People were prohibited from accessing and expanding their farming areas in the national park, threatening their livelihoods. The livelihood diversity index (LDI) and livelihood asset index (LAI) were used to explore the livelihood systems of these communities. This study also examines the effect of livelihood assets on livelihood diversity and analyzes livelihood strategy choices using Giddens’ structuration theory. A quantitative survey combined with in-depth interviews was conducted in two villages with different land types: wetlands (rice fields) and drylands (farmlands). This study found that the communities diversified their livelihoods into eight types of livelihood strategies. Almost all livelihood indicators were different, and the differences in livelihood asset indicators affected the LDI. As a process of structuration, communities have diversified their livelihoods into farm (e.g., annual and perennial crops), off-farm (e.g., farm wages), and non-farm (e.g., services and government transfer) activities. Rural households have modified their social and physical structures to secure their livelihoods by optimizing agricultural intensification technologies or by seeking non-agricultural income. Households decide whether to specialize or diversify their livelihoods based on factors such as the area of cultivated land, number of crops cultivated, distance of the farming location from the house, total household income, non-farm income, and reciprocal relationships.